Biomaterial dental application of biphasic calcium phosphate (BCP) - Masudi, Sam'an Malik (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
To determine the characterization of calcium phosphate doped with zirconia and beta-tricalcium phosphate (J3-TCP) by Scanning Electron Microscope-Energy Dispersive X-ray (SEM-EDX), Transmission Electron Microscope (TEM), Fourier Transform Infrared (FTIR) and X-ray Diffraction (XRD) techniques.